Gente pobre, gente rica nas florestas da Amazônia - Martinez, Paulo Henrique [UNESP] (My University, 2010)
The diversity of social relations in the Amazon region is responsible for the complexity that generalized and simplified ideas conceal in the understanding of its Environmental History. Recent historiography on the North of Brazil shows that this diversity is not to be neglected, under the risk of perpetuating stereotypes and reproducing in common sense social and economic aspects that often lie at the basis of cultural actions, projects and values that push the destruction of the environment, the fragility of citizenship and the uncertainties about the future that hover over the Amazon in the 21st century.

A diversidade de relações sociais na região amazônica responde pela complexidade que idéias generalizantes e simplificadoras ocultam na compreensão de sua História Ambiental. A historiografia recente sobre o norte do Brasil mostra que esta diversidade não pode ser negligenciada, sob o risco de perpetuar estereótipos e reproduzir no senso comum aspectos sociais e econômicos que, muitas vezes, estão na base de ações, projetos e valores culturais que movem a destruição do meio ambiente, a fragilidade da cidadania e as incertezas de futuro que pairam sobre a Amazônia no século XXI.
Keywords: The Amazonia; Environmental history; Historiography; Amazônia; História ambiental; História do Brasil; Historiografia; Meio ambiente